(untitled) - Samson, Fred B (New York, 1996)
This book has emerged as the new paradigm for managing public and private land in the United States. It combine the principles of ecoysstem-level ecology with the broad-scale policy requirements of resource and public land management
Keywords: biological diversity conservation,ecosystem management